Confidence : a novel - Frumkin, Rafael (Simon & Schuster, 2023)
"At seventeen, Ezra Green doesn't have a lot going for him: he's shorter than average, snaggle-toothed, internet-addicted, and halfway to being legally blind. He's also on his way to Last Chance Camp, the final stop before juvie. But Ezra's summer at Last Chance turns life-changing when he meets Orson, brilliant and Adonis-like with a mind for hustling. Together, the two embark upon what promises to be a fruitful career of scam artistry. But when they try to pull off their biggest scam yet - Nulife, a corporation that promises its consumers a lifetime of bliss - things start to spin wildly out of control"--